Difficult Airway Management in a Pediatric Patient with Parapharyngeal Mass: Case Report - Farnaz Shahabi Shojaei; Nastaran Sadat Mahdavi; Hasanali Ahmadi; Gholamreza Ebrahimisaraj (Archives of Anesthesia and Critical Care, 2026)
Critical airway incidents in children are among common anesthetic concerns. Due to limited apnea tolerance, any delay in airway management can quickly lead to severe complications. Unique pediatric anatomical features such as a large epiglottis, narrowed subglottic space, prominent occiput, elevated larynx position, and enlarged tongue can heighten the risk of airway obstruction. In this report, we presented a case of compromised airway due to a parapharyngeal mass in a 7-year-old patient, managed without complications.